Central European Countries and The Smooth Adjustment Hypothesis - Stanislav Černoša (Naše gospodarstvo/Our economy, 2012)
This paper analyses bilateral trade between the Czech Republic, Poland, and Slovenia as Central European Countries (CEC-3) and the 15 European member states (EU-15). The study briefly presents a modified theory of customs unions; discusses results of the measurement of vertical intra-industry trade between the Czech Republic, Poland and Slovenia in trade with the EU-15; and identifies other important factors that define vertical intra-industry trade between the CEC-3 and EU-15 members. The aim of this paper is to test the smooth adjustment hypothesis (SAH), which predicts that a high level of total intra-industry trade is positively related to low adjustment costs.The traditional theory of customs unions supposes that members of customs unions or other regional trading arrangements have different relative factor endowments, which— under free trade conditions—results in inter-industry specialisation. Consequently costs of adjustments are smaller in the case of more developed member countries and greater in the case of less developed member countries. The modified theory of customs unions predicts that reduced trade barriers within the union will lead countries to intra- industry specialisation, which will have important implications for the short-run costs of adjustment—namely, the costs of adjustment will be smaller for all members of the customs union irrespective of their stage of development. Although the modified version of customs unions theory assumes that the SAH is valid, this paper confirms the view of many other authors that this hypothesis is doubtful.